The opposite effects of high-sucrose and high-fat diet on Fatty Acid oxidation and very low density lipoprotein secretion in rat model of metabolic syndrome - Cahova, Monika; Dankova, Helena; Palenickova, Eliska; Papackova, Zuzana; Kazdova, Ludmila (Journal of nutrition and metabolism, 2012)
Aims. To determine the effect of two different diets (high-sucrose (HS) and high-fat (HF)) on the main metabolic pathways potentially contributing to the development of steatosis: (1) activity of the liver lysosomal and heparin-releasable lipases; (2) fatty acid (FFA) oxidation; (3) FFA synthesis de novo; (4) VLDL output in vivo in a rat model of metabolic syndrome (MetS), hereditary hypertriglyceridemic (HHTg) rats fed HS or HF diets. Results. Both diets resulted in triacylglycerol (TAG) accumulation in the liver (HF > HS). The intracellular TAG lipolysis by lysosomal lipase was increased in both groups and positively correlated with the liver TAG content. Diet type significantly affected partitioning of intracellular TAG-derived fatty acids among FFA-utilizing metabolic pathways as HS feeding accentuated VLDL secretion and downregulated FFA oxidation while the HF diet had an entirely opposite effect. FFA de novo synthesis from glucose was significantly enhanced in the HS group (fed ≫ fasted) while being completely eradicated in the HF group. Conclusions. We found that in rats prone to the development of MetS associated diseases dietary-induced steatosis is not simply a result of impaired TAG degradation but that it depends on other mechanisms (elevated FFA synthesis or attenuated VLDL secretion) that are specific according to diet composition.